ANALYSIS OF STUDENTS' DIFFICULTIES IN SOLVING ESSAY PROBLEMS BASED ON MATHEMATICAL CONNECTIONS REVIEWED BY SELF-CONFIDENCE - Sari, Wulan; Irma, Ade; Fitraini, Depi (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This study aims to identify and describe students’ difficulties in solving essay-type problems based on their mathematical connection abilities in relation to self-confidence. This research employs a qualitative approach using a case study method. The subjects of the study were nine eighth-grade students at SMPN 40 Pekanbaru. Data were collected through triangulation techniques, including a mathematical connection ability test, a self-confidence questionnaire, and structured interviews. Data analysis consisted of data reduction, data display, and conclusion drawing. The results show that students with high self-confidence are able to solve problems well and appropriately connect mathematical concepts. Students with moderate self-confidence still experience difficulties in determining correct solutions, lack accuracy in calculations, and do not complete solution steps thoroughly. Meanwhile, students with low self-confidence face difficulties in almost all aspects, particularly in understanding and applying mathematical concepts and in solving verbal problems. These findings indicate that self-confidence plays an important role in students’ mathematical connection abilities. Therefore, learning strategies that can enhance students’ self-confidence are needed to optimally develop their mathematical connection skills. Penelitian ini bertujuan untuk mengidentifikasi dan mendeskripsikan kesulitan siswa dalam menyelesaikan soal uraian berdasarkan kemampuan koneksi matematis yang ditinjau dari self-confidence. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus. Subjek penelitian adalah sembilan siswa kelas VIII SMPN 40 Pekanbaru. Pengumpulan data dilakukan melalui triangulasi, yaitu tes kemampuan koneksi matematis, angket self-confidence, dan wawancara terstruktur. Analisis data meliputi reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa siswa dengan self-confidence tinggi mampu menyelesaikan soal dengan baik serta mengaitkan konsep matematis secara tepat. Siswa dengan self-confidence sedang masih mengalami kesulitan dalam menentukan solusi, kurang teliti dalam perhitungan, dan belum menyelesaikan langkah secara tuntas. Sementara itu, siswa dengan self-confidence rendah mengalami kesulitan pada hampir seluruh aspek, terutama dalam memahami dan menerapkan konsep matematika serta menyelesaikan soal verbal. Temuan ini menunjukkan bahwa self-confidence berperan penting dalam kemampuan koneksi matematis siswa. Oleh karena itu, diperlukan strategi pembelajaran yang dapat meningkatkan kepercayaan diri siswa agar kemampuan koneksi matematis berkembang secara optimal.